Exploring Tax Audits Instrument Validation: Perceptions Of Tax Inspectors At A Tax Office In Bandung City - Ai Hasanah; Iwan Sidharta; Siti Mialasmaya; Siti Nurpadhilah; Risna Amel Putriyani (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2022)
The state's critical role in tax revenue is essential for national development's sustainability and smooth running. One way to increase tax revenue is to conduct tax audits on potentially problematic taxpayers. This study aims to explore the tax audit instrument. Researchers tested the statement instrument to measure tax audits from employee perceptions directly related to tax audits, with as many as 40 people at one tax office in Bandung. The researcher used an exploratory factor analysis approach with the principal axis factor and oblimin extraction methods. The calculation results show the KMO value of 64.2%; the tax audit variable form into four factors. Furthermore, a simple calculation using the Partial Least Square (PLS) approach shows adequate validity and reliability values. The calculation results indicate that the statement items developed from the aspects of the audit, implementation, and reporting of the tax audit results meet the initial criteria to become an indicator of measuring the tax audit instrument. The study results provide an adequate tax audit instrument; however, further testing needs to validate this instrument to use in general.